An in vitro system evaluation of the rumen microbiome and rumen fermentation characteristics as a result of differing feed additives - Reyes, Arquimides A., author; Delmore, Robert J., advisor; Belk, Keith E., committee member; Engle, Terry E., committee member; Woerner, Dale R., committee member; Holt, Timothy N., committee member (Colorado State University. Libraries, 2019)
To view the abstract, please see the full text of the document.
Keywords: probiotics; rumen nutrition; rumen microbiome; feed additives